2022
DOI: 10.3390/su14148469
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Innovation Orientation of High-Tech SMEs “Small and Mid-Sized Enterprises in China” on Innovation Performance

Abstract: Mass entrepreneurship and innovation refer to encouraging the broad masses of the people, including industry, agriculture, commerce, education, and soldiers, to participate in entrepreneurship, encouraging all Chinese people to participate in innovation, which Premier Li put forward at the 2014 Summer Davos Forum in Tianjin. After seven years of development, the innovation orientation of mass entrepreneurship and innovation has become an important engine leading China’s economic growth in the future. This rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…This is an era of globalization where managers and responsible executives need to be competitive in the market to gain superior performance in their companies. However, building a BMI is not automatic; it takes talent and resources to do so [140,141].…”
Section: Discussionmentioning
confidence: 99%
“…This is an era of globalization where managers and responsible executives need to be competitive in the market to gain superior performance in their companies. However, building a BMI is not automatic; it takes talent and resources to do so [140,141].…”
Section: Discussionmentioning
confidence: 99%
“…The team innovation performance enables employees to promote creativity and innovative ideas. Technology is critical in cultivating firms' innovation performances [42]. Positive organizational attitudes enable emerging digital phenomena (i.e., affinity towards technology) foster businessrelated innovation processes.…”
Section: Corporate Affinity For Technology and Team Innovation Perfor...mentioning
confidence: 99%
“…It is in line with what (Singh & Sushil, 2004) reported that production flexibility dealt with the effective use of company resources to create various products or services to meet various demands regardless of environmental uncertainty with minimum impact on costs and overall objectives. Moreover, flexibility significantly impacts the sustainability of competitive advantage (Tong & Rahman, 2022).…”
Section: Flexible-product-focused Short-term Oriented and Resilient S...mentioning
confidence: 99%